High myopia in Greater Beijing School Children in 2016 - Guo, Yin; Jonas, Jost B. (PLOS ONE, 2017)
Purpose To assess prevalence and associated factors of myopia and high myopia in schoolchildren in Greater Beijing. Methods The school-based, cross-sectional Greater Beijing School Children Myopia study was carried out in the year 2016 in 54 schools randomly selected from 15 districts in Beijing. Non-cycloplegic auto-refractometry of the right eyes was performed. Results The study included 35,745 (99.4%) out of 35,968 eligible pupils with a mean age of 12.6±3.4 years (range 6-18 years). Prevalence of myopia defined as myopic refractive error of ≥-0.50 diopters (D),≥-1D,≥-6D,≥-8D and ≥-10D was 70.9%(95% confidence intervals (CI):70.5,71.4), 60.9% (95%CI:60.4,61.4), 8.6%(95%CI:8.4,8.9), 2.2%(95%CI:2.0,2.4), and 0.3% (95%CI:0.3,0.4), respectively. The frequency of high myopia (≥-6D, ≥-8D, ≥-10D) increased from 1.5% (95%CI:1.0,2.0), 0.4% (95%CI:0.1,0.6) and 0.1% (95%CI:0.00,0.02), respectively in 10-year-olds to 19.4% (95%CI:17.3,21.6), 5.2% (95%CI:4.0,6.4) and 0.9% (95%CI:0.4,1.5), respectively, in 18-year-olds. Mean refractive error in the 18-year-olds was -3.74±2.56D (median:-3.63D;range:-19.6D to + 6.25D). Higher prevalence of high myopia (≥-6D and ≥-8D) was correlated (all P<0.001) with older age (OR:1.18, and 1.15, respectively), female gender (OR: 1.44 and 1.40, respectively), higher body mass index (OR: 1.02 and 1.03, respectively), taller body height (OR: 1.03 and 1.02, respectively), urban region of habitation (OR: 1.26 and 1.33, respectively) and higher school type (OR:1.57 and 2.22, respectively). Prevalence of severe high myopia (≥-10D) was associated only with older age (P<0.001; OR: 1.44; 95%CI: 1.31, 1.59) but not with any education-related parameter such as higher school type (P = 0.48), urban region of habitation (P = 0.07) or female gender (P = 0.37). Conclusion In this most recent survey, prevalence of high myopia (≥-6D:19.4%;≥-8D:5.2%;≥-10D:0.9%) in 18-year-old school children was higher than in previous surveys from mainland China. In contrast to minor high myopia and moderate high myopia (defined as myopic refractive error of <-10D), severe high myopia (myopic refractive error ≥-10D) was not strongly correlated with educational parameters.